Care plus study: a multi-site implementation of early palliative care in routine practice to improve health outcomes and reduce hospital admissions for people with advanced cancer: a study protocol - Jennifer Philip; Roslyn Le Gautier; Anna Collins; Anna K. Nowak; Brian Le; Gregory B. Crawford; Nicole Rankin; Meinir Krishnasamy; Geoff Mitchell; Sue-Anne McLachlan; Maarten IJzerman; Robyn Hudson; et al. (BMC, 2021)
Abstract Background Current international consensus is that 'early' referral to palliative care services improves cancer patient and family carer outcomes. In practice, however, these referrals are not routine. An approach which directly addresses identified barriers to early integration of palliative care is required. This protocol details a trial of a standardized model of early palliative care (Care Plus) introduced at key defined, disease-specific times or transition points in the illness for people with cancer. Introduced as a 'whole of system' practice change for identified advanced cancers, the key outcomes of interest are population health service use change. The aims of the study are to examine the effect of Care Plus implementation on (1) acute hospitalisation days in the last 3 months of life; (2) timeliness of access to palliative care; (3) quality and (4) costs of end of life care; and (5) the acceptability of services for people with advanced cancer. Methods Multi-site stepped wedge implementation trial testing usual care (control) versus Care Plus (practice change). The design stipulates 'control' periods when usual care is observed, and the process of implementing Care Plus which includes phases of planning, engagement, practice change and evaluation. During the practice change phase, all patients with targeted advanced cancers reaching the transition point will, by default, receive Care Plus. Health service utilization and unit costs before and after implementation will be collated from hospital records, and state and national health service administrative datasets. Qualitative data from patients, consumers and clinicians before and after practice change will be gathered through interviews and focus groups. Discussion The study outcomes will detail the impact and acceptability of the standardized integration of palliative care as a practice change, including recommendations for ongoing sustainability and broader implementation. Trial registration Australian New Zealand Clinical Trials Registry ACTRN 12619001703190 . Registered 04 December 2019.